USING THE MOORE'S THEORY TO EXPLAIN PRESERVICE TEACHERS’ DIFFICULTIES IN PROVING OF THE TRIANGLE SUM THEOREM - Hartono, Sugi; Siswono, Tatag Yuli Eko; Ekawati, Rooselyna; Bonyah, Ebenezer (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
This study aims to analyze the difficulties of preservice teachers’ in proving the triangle sum theorem. The method of this study is used a qualitative method with 58 of preservice mathematics teacher studying for a Bachelor of Education degree in Universitas Negeri Surabaya, Indonesia. The authors analysed the written responses to a 1 item worksheet and also conducted interviews with seven of the participants. The analysis of the data was guided by Moore’s theory which was used to identify difficulties of preservice teachers’ in proving of the triangle sum theorem. The results showed that still many of preservice teachers still difficulties in proving of the triangle sum theorem. There were 38% of preservice teachers who answered correctly and 62% of preservice teachers answered incorrectly in compiling proof. It was found that several preservice teachers had difficulties in compiling proofs, namely 30 preservice teachers had difficulty understanding the concept, 2 preservice teacher's did not understand the language and mathematical notation and 4 preservice teacher's had difficulty starting the proof. The novelty of this research is introducing a new theoretical analysis related to the difficulty in proving the fundamental theorem of geometry, namely Moore's theory. This study recommends that preservice teacher’s should be given solution through scaffolding to help preservice teacher's understand the concept of proof so that students can compiling proofs with correct.